2014
DOI: 10.1098/rsif.2014.0101
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and biological properties of the gradient coating on polyamide substrate for bone substitute

Abstract: Fabrication of bioactive and mechanical matched bone substitutes is crucial for clinical application in bone defects repair. In this study, nano-hydroxyapatite/ polyamide (nHA/PA) composite was coated on injection-moulded PA by a chemical corrosion and phase-inversion technique. The shear strength, gradient composition and pore structure of the bioactive coating were characterized. Osteoblast-like MG63 cells were cultured on pure PA and composite-coated PA samples. The cells' adhesion, spread and proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Several studies measured the shear strength/modulus of the bone bond with different implant materials through the push-out test and obtained higher bond strength by the time. For example, Huang et al [ 40 ] tested the in vivo performance of two implant materials in a rabbit model. Their push-out test showed higher shear strength for both materials at week 12 compared to week 4.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies measured the shear strength/modulus of the bone bond with different implant materials through the push-out test and obtained higher bond strength by the time. For example, Huang et al [ 40 ] tested the in vivo performance of two implant materials in a rabbit model. Their push-out test showed higher shear strength for both materials at week 12 compared to week 4.…”
Section: Discussionmentioning
confidence: 99%
“…29 It means that the calciumethanol complex molecules open the hydrogen bonding between the polymer chains. 23 As a result, the polymer chains at the surface of the substrate become loose and complex with calcium ions. 23,27 The increased peak at 1024 cm À1 corresponding to the C]O groups in Fig.…”
Section: Pretreatment Of Pa Substratementioning
confidence: 99%
“…23 As a result, the polymer chains at the surface of the substrate become loose and complex with calcium ions. 23,27 The increased peak at 1024 cm À1 corresponding to the C]O groups in Fig. 2 verify this point.…”
Section: Pretreatment Of Pa Substratementioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the physicochemical and biological properties of nylon 6 scaffolds, a calcium phosphate ultrathin layer was coated on the electrospun scaffolds resulted in a desirable nanocomposite for bone tissue regeneration 87 . Animal model studies using nano HA/nylon composite implant were also conducted, and the results demonstrated good contact between the bone and implant 88 . Besides calcium phosphate‐based materials, a study took advantage of a calcium zirconium silicate mineral called baghdadite to be concocted with nylon 6 for bone tissue regeneration 89 .…”
Section: Regenerative Medicinementioning
confidence: 99%